Influência do pH na estabilidade dos coacervatos de prata como precursores vítreos - Montanari, Bianca [UNESP]; Vast, Pierre [UNESP]; Martines, Marco Antonio Utrera [UNESP]; Ribeiro, Sidney José Lima [UNESP]; Messaddeq, Younes [UNESP] (Editora Unesp, 2002)
Neste trabalho, usando o processo de coacervação, foi estudado o sistema NaPO3/AgNO3/H2O. Determinou-se o domínio de coacervação a partir de diferentes concentrações de NaPO3 e AgNO3 e a influência do pH na estabilização do coacervato foi determinada. Os coacervatos obtidos em pH ~ 5 apresentam maior região de estabilidade.

In this work, using coacervation process, the influence of the pH in the stability of the coacervates of the NaPO3/AgNO3/H2O system was studied. The coacervate domain was established using different concentrations of NaPO3 and AgNO3 and the influence of the pH in the stability of the coacervate was putfoward. The coacervates obtained at pH ~ 5 present highest stability.
Influence of the pH in the stability of the silver coacervate by vitreous precursors
Keywords: coacervato; vidros e fosfatos; coacervate; glasses and phosphates